Influencer marketing in the tourism industry: A systematic review of theories, methods, and findings - Sadakat Akram; Rukhsana Majeed (Borneo Novelty Publishing, 2026)
Purpose - This study aims to analyse behavioural outcomes shaped by social media influencers in tourist decision-making, identify dominant theoretical and methodological approaches, and examine how influencer marketing has been applied within the tourism sector.Methodology/Design/Approach - A systematic literature review was conducted using the PRISMA approach. Publications from 2010 to 2025 indexed in Web of Science and Scopus were screened. Following the stages of identification, screening, eligibility, and inclusion, 32 relevant studies on influencer marketing in tourism were selected for in-depth analysis.Findings - The results indicate that influencer marketing has become an effective communication tool for many organisations; however, academic research in tourism remains limited and methodologically fragmented. Key factors influencing travel intention, destination loyalty, word-of-mouth, and experience sharing include credibility, authenticity, emotional engagement, parasocial interaction, and influencer–destination fit. Emerging themes such as virtual influencers, platform-specific content, ethical promotion, and green tourism messaging are also evident. Overall, influencer marketing significantly affects tourist behaviour when aligned with audience preferences, destination branding, and emotionally engaging narratives, although contextual differences highlight the need for comparative and integrative research.Originality/Value - This study contributes to tourism literature by mapping the evolution of influencer-based destination promotion, identifying theoretical and empirical gaps, and proposing directions for future research while offering practical insights for data-driven influencer collaboration strategies.